Investigation the amount of Fluoride in drinking water sources in urban and rural areas of Neyshabur in 2017 - Sima Zamand; hossein alidadi; Vahid Taghavimanesh (Mashhad University of Medical Sciences, 2018)
Background: Fluoride is one of the 14 essential elements for organisms' lives. Since the body's greatest need for fluoride should be supplied through drinking water, determination of the amount of fluoride in drinking water has great importance. The aim of this study was to measure the concentrations of fluoride in sources of drinking water in urban and rural areas of Neyshabur in 2017 and compare it with existing standards.   Materials and Methods:This descriptive cross-sectional was conducted on urban and rural drinking water sources in Neyshabur in 2017. A total of 100 water samples were randomly collected from different sources in Neyshabur. The collected samples were then transferred to the Neyshabur Water and Wastewater Laboratory and the proportion of fluoride ion was measuredusing a spectrophotometer DR 2000 at 580 nm.   Results:The average concentration of fluoride in rural resources was obtained0.567± 0.12 mg/lin wells and 0.69 ± 0.13 mg/lin springs. The average concentration of fluoride in plain areas (0.662 ± 0.14 mg/l) was higher than mountainous areas (0.505 ± 0. 2 mg / l). The average concentrations of fluoride in urban wells, in urban reservoirs and in the water distribution networkwere (0.602 ± 0.034 mg / l),(0.597 ± 0.030 mg / L) and (0.595±0.039 mg /l) respectively.   Conclusion:The average concentration of fluoride in some water sources was lower than the standard level.Therefore, more study is needed to evaluate the daily fluoride intake in a variety of methods, and if the fluoride intake is less than standard level, adjustment of fluoride in water sources will benecessary for dental health.